Targeted therapies in HPV-positive and -negative HNSCC - alteration of EGFR and VEGFR-2 expression in vitro - Kramer, Benedikt; Hock, Clemens; Birk, Richard; Sauter, Alexander; Hörmann, Karl; Schultz, Johannes D.; Aderhold, Marc Christoph (Anticancer research, 2016)
Background: Angiogenesis plays a crucial role in the formation and progression of tumor growth in head and neck squamous cell carcinoma (HNSCC). The tyrosine kinase receptors epidermal growth factor receptor (EGFR) and vascular endothelial growth factor receptor (VEGFR) are essential for mediation of pro-angiogenic signals. Nilotinib, dasatinib, erlotinib and gefitinib are tyrosine kinase inhibitors and approved as targeted therapies for several tumor entities other than HNSCC. In this study, we sought to evaluate the alteration of EGFR and VEGFR-2 expression by these tyrosine kinase inhibitors with respect to the human papillomavirus (HPV)-status in squamous cell carcinoma (SCC) tumor cells. Materials and Methods: Expression patterns of EGFR and VEGFR-2 were determined by enzyme linked immunosorbent assay (ELISA) in HNSCC 11A, HNSCC 14C and p-16-positive CERV196 tumor cell lines. These cells were incubated with nilotinib, dasatinib, erlotinib and gefitinib (5-20μmol/l) and compared to a chemonaive control. The incubation time was 24, 48, 72 and 96 h. Results: All tested substances led to a statistically significant reduction (p<0.05) of EGFR protein expression levels in HPV-negative cells compared to the negative control. Surprisingly, a statistically significant increase in VEGFR-2 expression was observed after exposure to all tested substances especially after exposure to erlotinib treatment. Conclusion: Nilotinib, dasatinib, erlotinib and gefitinib cause significant changes in protein expression of EGFR and VEGFR-2 in vitro. Besides the anti-angiogenic impact of the substances, as shown for the decrease of EGFR expression, we also observed an increase of VEGFR-2 expression. These contradictive effects could be interpreted as a compensatory up-regulation by the tumor cell.
Gesehen am 24.06.2019